Fine granularity sentiment analysis method for automobile comments - WU YUNIAN; LIU HAILONG (2025)
The invention discloses a fine granularity sentiment analysis method for automobile comments. The method comprises the following steps: S100, carrying out short sentence segmentation and word segmentation on training corpora in a training corpus; s200, performing word vectorization on the segmented words; s300, carrying out similar word clustering on the subject words; s400, extracting high-frequency phrases from the training corpora in the training corpus, and carrying out classification and labeling on the high-frequency phrases; s500, classifying the short sentences; and S600, performing sentiment analysis on the classified short sentences. According to the fine granularity sentiment analysis method for the automobile comments, accurate feature extraction can be carried out on the automobile comments, and the method has important research significance for collecting product use feedback. 本发明公开一种汽车评论的细颗粒度情感分析方法，包括如下步骤：S100，对训练语料库中的训练语料进行切分短句以及分词；S200，对分词进行词语向量化；S300，对主题词进行相似词聚类；S400，对训练语料库中的训练语料提取高频词组并分类标注；